Habitat preferences of Phoebetria albatrosses in sympatry and allopatry - Lily K. Bentley; Richard A. Phillips; Tegan Carpenter‐Kling; Robert J. M. Crawford; Richard J. Cuthbert; Karine Delord; Ben J. Dilley; Azwianewi B. Makhado; Peter I. Miller; Steffen Oppel; Pierre A. Pistorius; Peter G. Ryan; et al. (Journal of Biogeography, 2024)
Aim Competition is often proposed to drive niche segregation along multiple axes in speciose communities. Understanding spatial partitioning of foraging areas is particularly important in species that are constrained to a central place. We present a natural experiment examining variation in habitat preferences of congeneric Southern Ocean predators in sympatry and allopatry. Our aim was to ascertain consistency of habitat preferences within species, and to test whether preferences changed in the presence of the congener. Location Southern Hemisphere. Taxon Multiple colonies of both species within the genus Phoebetria (sooty albatrosses). Methods The two Phoebetria albatrosses breed on islands located from ~37–55°S – sooty albatrosses ( P. fusca ) in the north and light‐mantled albatrosses ( P. palpebrata ) in the south – with sympatric overlap at locations ~46–49°S. We analysed GPS and PTT tracks from 87 individuals and multiple remotely sensed environmental variables using GAMs, to determine and compare the key factors influencing habitat preference for each species at each breeding colony. Results While foraging habitat preferences are consistent in light‐mantled albatrosses, there is divergence of preferences in sooty albatrosses depending on whether they are in sympatry with their congener or in allopatry. Main Conclusions This study represents the most comprehensive work on this genus to date and highlights how habitat preferences and behavioural plasticity may influence species distributions under different competitive conditions.

Biological invasions are a population‐level rather than a species‐level phenomenon - Phillip J. Haubrock; Ismael Soto; Danish A. Ahmed; Ali R. Ansari; Ali Serhan Tarkan; Irmak Kurtul; Rafael L. Macêdo; Adrián Lázaro‐Lobo; Mathieu Toutain; Ben Parker; Dagmara Błońska; Simone Guareschi; et al. (Global Change Biology, 2024)
Biological invasions pose a rapidly expanding threat to the persistence, functioning and service provisioning of ecosystems globally, and to socio‐economic interests. The stages of successful invasions are driven by the same mechanism that underlies adaptive changes across species in general—via natural selection on intraspecific variation in traits that influence survival and reproductive performance (i.e., fitness). Surprisingly, however, the rapid progress in the field of invasion science has resulted in a predominance of species‐level approaches (such as deny lists), often irrespective of natural selection theory, local adaptation and other population‐level processes that govern successful invasions. To address these issues, we analyse non‐native species dynamics at the population level by employing a database of European freshwater macroinvertebrate time series, to investigate spreading speed, abundance dynamics and impact assessments among populations. Our findings reveal substantial variability in spreading speed and abundance trends within and between macroinvertebrate species across biogeographic regions, indicating that levels of invasiveness and impact differ markedly. Discrepancies and inconsistencies among species‐level risk screenings and real population‐level data were also identified, highlighting the inherent challenges in accurately assessing population‐level effects through species‐level assessments. In recognition of the importance of population‐level assessments, we urge a shift in invasive species management frameworks, which should account for the dynamics of different populations and their environmental context. Adopting an adaptive, region‐specific and population‐focused approach is imperative, considering the diverse ecological contexts and varying degrees of susceptibility. Such an approach could improve and refine risk assessments while promoting mechanistic understandings of risks and impacts, thereby enabling the development of more effective conservation and management strategies.

Understanding connected surface-water/groundwater systems using Fourier analysis of daily and sub-daily head fluctuations - R. I. Acworth; Gabriel C. Rau; Andrew M. McCallum; Martin S. Andersen; Mark O. Cuthbert (Hydrogeology Journal, 2015)

Demographic history of a recent invasion of house mice on the isolated I sland of G ough - Melissa M. Gray; Daniel Wegmann; Ryan J. Haasl; Michael A. White; Sofia I. Gabriel; Jeremy B. Searle; Richard J. Cuthbert; Peter G. Ryan; Bret A. Payseur (Molecular Ecology, 2014)
Island populations provide natural laboratories for studying key contributors to evolutionary change, including natural selection, population size and the colonization of new environments. The demographic histories of island populations can be reconstructed from patterns of genetic diversity. House mice ( M us musculus ) inhabit islands throughout the globe, making them an attractive system for studying island colonization from a genetic perspective. G ough I sland, in the central S outh A tlantic O cean, is one of the remotest islands in the world. House mice were introduced to G ough I sland by sealers during the 19th century and display unusual phenotypes, including exceptionally large body size and carnivorous feeding behaviour. We describe genetic variation in G ough I sland mice using mitochondrial sequences, nuclear sequences and microsatellites. Phylogenetic analysis of mitochondrial sequences suggested that G ough I sland mice belong to M us musculus domesticus , with the maternal lineage possibly originating in E ngland or F rance. Cluster analyses of microsatellites revealed genetic membership for G ough I sland mice in multiple coastal populations in W estern E urope, suggesting admixed ancestry. G ough I sland mice showed substantial reductions in mitochondrial and nuclear sequence variation and weak reductions in microsatellite diversity compared with W estern E uropean populations, consistent with a population bottleneck. Approximate B ayesian computation ( ABC ) estimated that mice recently colonized G ough I sland (~100 years ago) and experienced a 98% reduction in population size followed by a rapid expansion. Our results indicate that the unusual phenotypes of G ough I sland mice evolved rapidly, positioning these mice as useful models for understanding rapid phenotypic evolution.

Towards best practice for assessing the impacts of climate change on groundwater - I. P. Holman; D. M. Allen; M. O. Cuthbert; P. Goderniaux (Hydrogeology Journal, 2012)

Short and long term effects of antipsychotic medication on smooth pursuit eye tracking in schizophrenia - S. Hutton; T. Crawford; H. Gibbins; I. Cuthbert; T. Barnes; C. Kennard; E. Joyce (Psychopharmacology, 2001)